(untitled) (Bangladesh Journal of Pharmacology, 2018)
Anti-snake venom therapy is the only treatment for snake bite but leads to acute and chronic conditions which may be severe. The medicinal plants have gained importance over years to find an effective alternative to anti-snake venom. The present study focused on evaluating the potential of Clerodendrum serratum for the anti-snake venom activity. Phytochemicals were extracted from the C. serratum with different solvents. The ethyl acetate and methanolic extracts were found to neutralize the major enzyme toxins (phospholipase A2, protease and hyaluronidase) of Bungarus caeruleus and Daboia russelii venom at a concentration of 100 µg/mL. The fibrinogenolytic activity of both the venoms were neutralized. The study proves that the plant C. serratum possesses certain compounds which inhibit the toxins present in the venom of B. caeruleus and D. russelii. Video Clip of Methodology: Hyaluronidase assay: 3 min 30 sec Click to watch